(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the knowledge and practice of safe use of pesticides and identify associated factors among the hired sprayers in Thanh Binh district, Dong Thap province in 2021. Methods: A cross-sectional study was conducted in four communes of Thanh Binh district with a sample size of 200 hired sprayers. Descriptive and analytic biostatistics techniques were applied at significance level of 0.05. Results: The percentage of researchers with correct knowledge and appropriate practices was above the average level, i.e. 64.5% and 63%, respectively. The researchers who participated in the training had higher correct practice than those who did not participate in the training (p < 0.05%). Conclusion: The appropriate practices of safe use of pesticides average. Participation in training course on pesticides was associated to the appropriate practices of safe pesticide usage.